Hemi-Slant Warped Product Submanifolds of Nearly Kaehler Manifolds - Falleh R. Al-Solamy; Meraj Ali Khan (Abstract and Applied Analysis)
Hemi-slant warped product submanifolds of nearly Kaehler manifolds are studied and some interesting results are obtained. Moreover, an inequality is established for squared norm of second fundamental form and equality case is also discussed. The results obtained are also true if ambient manifold is replaced by a Kaehler manifold. These results generalize several known results in the literature.